The Implementation of the Black Box Method for Testing Smart Hajj Application Ministry of Religion - Alan Budi Kusuma; Novri Hadinata (Universitas Bina Darma, 2022)
This research was conducted to assist the Ministry of Religious Affairs in testing the quality and accuracy of the Haji Pintar application. The main purpose of testing is to design tests that systematically uncover types of errors that have not been detected before. The Haji Pintar application will be tested using the Black Box method thoroughly with respect to application functionality, interfaces , data structures or external database access, performance, initiation and termination errors, usage, benefits, and results obtained from the use of the application. In testing the Haji Smart application, there are 5 types of testing from the Black Box method. The value of the overall effectiveness of the Haji Pintar application is 83.75%. With this value, the Haji Pintar application has been running according to the expected functionality but there are still errors in the application that must be updated immediately regarding the cancellation information menu and the payment information menu, which experienced problems when checking the status of the cancellation process that the congregation submitted and checking the congregation portion. Hajj includes the right to pay off or not.